Family size, fertility preferences, and sex ratio in China in the era of the one child family policy: results from national family planning and reproductive health survey - Ding, Qu Jian (BMJ Publishing Group Ltd., 2006)
Objectives To examine the impact of the one child family policy in China on fertility, preferred family size, and sex ratio. Design Secondary analysis of data from the Chinese cross sectional national family planning and reproductive health survey, 2001. Interviews of representative sample of women aged 15-49. Results Data were obtained from 39 585 women, with a total of 73 202 pregnancies and 56 830 live births. The average fertility rate in women over 35 (n = 17 078) was 1.94 (2.1 in rural areas and 1.4 in urban areas) and for women under 35 (n = 11 543) 1.73 (1.25 and 1.79). Smaller families were associated with younger age, higher level of education, and living in an urban area. The male to female ratio was 1.15 and rose from 1.11 in 1980-9 to 1.23 for 1996-2001. Most women wanted small families: 35% preferred one child and 57% preferred two. Conclusion Since the one child family policy began, the total birth rate and preferred family size have decreased, and a gross imbalance in the sex ratio has emerged.